PSYCHOSOCIAL REPERCUSSIONS OF MENTAL DISORDER IN ADOLESCENTS IN FAMILY RELATIONS: SCOPE REVIEW - Leite, Roberto Corrêa; Saidel, Maria Giovana Borges; Oliveira, Danielle Leite de Lemos; Jamarim, Michelle Ferraz Martins; Campos, Claudinei José Gomes; Lima, Gerusa Marcondes Pimentel de Abreu (Cogitare Enfermagem, 2024)
Objective: Map the scientific production about the psychosocial repercussions of mental disorder in adolescents in family relationships. Method: Scope review based on the Joanna Briggs Institute framework, conducted in the databases: Virtual Health Library (VHL), PubMed, Cumulative Index to Nursing & Allied Health Literature (CINAHL), Scopus, Web of Science, and PsycInfo. Two reviewers independently selected the articles published between January 2015 and July 2023. Results: Nineteen studies were included, revealing three thematic categories, consisting of emotional repercussions on the subjective well-being of family relationships, unfavorable emotional repercussions in family relationships, and social repercussions. Conclusion: One should seek improvement in the triadic interactions between the family, the adolescent, and health professionals to support them in solving dilemmas and unfavorable psychosocial repercussions, as well as prioritize the protection and strengthening of well-being and quality in relationships.